2020
DOI: 10.1038/s41598-020-66726-y
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Remediation of the difficult-to-return zone in Tomioka Town, Fukushima Prefecture

Abstract: Temporal variations in ambient dose rates in a restricted area designated as "difficult-to-return" for residents of Tomioka Town, Fukushima Prefecture were evaluated in a car-borne survey during 2018-2019. The median dose rates in the "Decontaminated area" in the difficult-to-return zone decreased rapidly from 1.0 μSv/h to 0.32 μSv/h; however, the median dose rates in the "Non-decontaminated area" and "Radioactive waste storage area" fluctuated between 1.1-1.4 μSv/h and 0.46-0.61 μSv/h, respectively. The detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 27 publications
1
24
0
Order By: Relevance
“…However, radiocesium was only detected at 2.4% of sites along the hiking trail and at 12.9% sites off the hiking trail 24 . When temporal variations in ambient dose rates in the difficult-to-return to areas of Tomioka Town were evaluated using the RADI-PROBE (car-based survey) during 2018-2019, we confirmed that the dose rates in the area had decreased dramatically due to decontamination efforts 25 . 137 Cs was detected at 3.8% to 93% of sites using the RADI-PROBE 25 , while the dose-forming artificial radionuclides 134 Cs and 137 Cs were only prevalent at some measuring sites (Supplementary S1) 24 .…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…However, radiocesium was only detected at 2.4% of sites along the hiking trail and at 12.9% sites off the hiking trail 24 . When temporal variations in ambient dose rates in the difficult-to-return to areas of Tomioka Town were evaluated using the RADI-PROBE (car-based survey) during 2018-2019, we confirmed that the dose rates in the area had decreased dramatically due to decontamination efforts 25 . 137 Cs was detected at 3.8% to 93% of sites using the RADI-PROBE 25 , while the dose-forming artificial radionuclides 134 Cs and 137 Cs were only prevalent at some measuring sites (Supplementary S1) 24 .…”
Section: Discussionmentioning
confidence: 57%
“…In addition, we did not characterize the soils along the Mt Okura hiking trail, although the findings of our previous study showed that dose-forming artificial radiocesium was prevalent in all surface soil samples (0-10 cm) collected in Tomioka Town in 2017 20 . However, in the present study, we used the RADI-PROBE for high and sensitive gamma-ray detection (typically 1400 cps per µSv/h for 137 Cs) 24,25,42 . Further investigations on individual doses and ambient doses under several weather conditions are needed.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate 137 Cs radioactivity levels in airborne dust, including resuspended soil particles that are due to 137 Cs contamination of the surface soil, the L‐RF values used in the present study were calculated using the following equation: K=C137sinvent/C137scont,where 137 Cs invent is the 137 Cs radioactivity level of airborne dust (Bq/m 3 ) and 137 Cs cont is the 137 Cs contamination in the surface soil layer (0–0.5 cm) (Bq/m 2 ) collected in the present study (Abe et al, 2021; Ochiai et al, 2016). Because the decontamination in the Yonomori district of the SRRB used the same schedule and technical methods, the surface soil contamination levels that were closest to the airborne dust sampling points (in time) were adopted as the reference values (Cui et al, 2020). Actually, there are some parks, agricultural lands, forests (the boundary with the SRRB), and deposited grounds around the “Building G” and “Building Y” sites at the SRRB in the Yonomori district (Supporting Information: Appendix ) (MOE, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…In particular, the national government and Tomioka town office pay attention to their internal radiation exposures due to the 137 Cs that is present around residents' houses, although they may not be directly exposed to airborne dust. Radiocesium has a relatively long half‐life, and still exists in soil and plant samples that were collected around the FDNPS, including Tomioka town (Cui et al, 2020 ; MHLW, 2018 ; Tomioka Town Office, 2021 ). Additionally, 134 Cs and 137 Cs were the dominant radionuclides comprising the indoor surface contamination of wooden houses located within the evacuation areas after the FDNPS accident, and there was a distance dependence from the FDNPS (Yoshida et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The main objective of the current study is to predict future air dose rates by using ARIMA model in a return zone , where the inhabitants entry is forbidden [29] and the annual cumulative dose is greater than 20 mSv [30]. Evaluating the radiological hazard indices relying on the output data.…”
Section: Jrncmentioning
confidence: 99%